Career values and proactive career behaviour among contemporary higher education students. Issue 5 (4th July 2019) - Jackson, Denise; Tomlinson, Michael
ABSTRACT: The paper draws on evidence from a survey of Australian and UK students ( N = 433) on students' career values and their relationship to their proactivity in career self-management. Much of the dominant approaches to careers have focused on career competencies and adaptability in the context of increased movement from traditional to more self-managed career trajectories. Limited attention has been given to the role of career values in shaping individuals' approaches to career management, particularly among higher education students. This study reveals data on a range of career values among students on a continuum between intrinsic and extrinsic careers. It revealed a preponderance of intrinsic career values and a clear relationship emerged on the strength of career values and levels of proactivity towards career management. Further, higher levels of intrinsic and extrinsic career values were reported for certain student groups. The article discusses the implications of these data for enhancing students' career planning and engagement.